2017
DOI: 10.1007/s00246-017-1600-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiac Function in Fetuses of Gestational Diabetic Mothers During the Second Trimester

Abstract: Fetuses of diabetic mothers may have structural or functional cardiac abnormalities which increase morbidity and mortality. Isolated functional abnormalities have been identified in the third trimester. The aim of the present study was to assess fetal cardiac function (systolic, diastolic, and global myocardial performance) in the second trimester in mothers with gestational diabetes, and also to relate cardiac function with glycemic control. Mothers with gestational diabetes mellitus referred for fetal cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 22 publications
5
43
0
Order By: Relevance
“…Other studies suggested that the MPA index has a more stable pattern with advancing gestation . Fetuses of diabetic mothers usually have a higher value for the MPI at all trimesters compared to controls . Although these results support impairment in both systolic and diastolic components of cardiac cycle in fetuses of diabetic mothers, some studies could not reveal any changes in the MPI index or E/A ratio in fetuses of diabetic mothers …”
Section: Functional Evaluationmentioning
confidence: 77%
See 4 more Smart Citations
“…Other studies suggested that the MPA index has a more stable pattern with advancing gestation . Fetuses of diabetic mothers usually have a higher value for the MPI at all trimesters compared to controls . Although these results support impairment in both systolic and diastolic components of cardiac cycle in fetuses of diabetic mothers, some studies could not reveal any changes in the MPI index or E/A ratio in fetuses of diabetic mothers …”
Section: Functional Evaluationmentioning
confidence: 77%
“…This may be attributed to the already lower E/A ratio that exists in fetuses of diabetic mothers at early gestation, as supported by studies evaluating the E/A ratio in the first trimester . Many other studies have also found a lower E/A ratio in fetuses of diabetic mothers compared with those of nondiabetic mothers in the second and third trimesters . At the same time, the E/A ratio can be measured lower in fetuses of diabetic mother compared to healthy controls even if blood glucose level is well regulated .…”
Section: Functional Evaluationmentioning
confidence: 83%
See 3 more Smart Citations